2022
DOI: 10.25259/sni_377_2022
|View full text |Cite
|
Sign up to set email alerts
|

The pharmaceutical industry is dangerous to health. Further proof with COVID-19

Abstract: Background: The COVID-19 period highlights a huge problem that has been developing for decades, the control of science by industry. In the 1950s, the tobacco industry set the example, which the pharmaceutical industry followed. Since then, the latter has been regularly condemned for illegal marketing, misrepresentation of experimental results, dissimulation of information about the dangers of drugs, and considered as criminal. Therefore, this study was conducted to show that knowledge is powerfully manipulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Future research should explore the impact of COI in social media on the perceptions, beliefs and behaviours of their users. Despite the extent of misinformation, and disinformation on social media during the COVID-19 pandemic,27 no study has assessed the prevalence of COI in that context. Interestingly, one study found a correlation between the amounts received by academic infectious diseases physicians from Gilead Sciences, producer of remdesivir and their public opposition to the use of hydroxychloroquine 28.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should explore the impact of COI in social media on the perceptions, beliefs and behaviours of their users. Despite the extent of misinformation, and disinformation on social media during the COVID-19 pandemic,27 no study has assessed the prevalence of COI in that context. Interestingly, one study found a correlation between the amounts received by academic infectious diseases physicians from Gilead Sciences, producer of remdesivir and their public opposition to the use of hydroxychloroquine 28.…”
Section: Discussionmentioning
confidence: 99%
“…This claim overlooks centuries-long evidence that the major declines in mortality by such diseases have been due not to mass vaccination but to improvements in nutrition, sanitation, and other social determinants of health [122][123][124][125] . It also overlooks historical and current evidence of grossly inadequate safety testing of vaccines 126 , of the conflicts of interest corrupting the vaccine "approval" process 127 , and of mounting vaccine injuries 128,129 . In sum, despite very high vaccination rates in their midst, academic institutions have consistently framed "vaccine hesitancy" and "uptake" as problems, a position, as we have argued, untenable on scientific, legal, and ethical grounds.…”
Section: Selected Covid-19 Responses In Academiamentioning
confidence: 99%